Kay Stone and Ruby Holder, 1960. - (:unkn) unknown (Forsyth County Public Library, 2009)
TCS 5-27-60 p.1.
Kay Stone and Ruby Holder, 1960.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth